2021
DOI: 10.1039/d1re00150g
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced methane conversion using Ni-doped calcium ferrite oxygen carriers in chemical looping partial oxidation systems with CO2 utilization

Abstract: Chemical looping partial oxidation (CLPO) is a novel technology for converting methane into high quality syngas that can be further converted into liquid fuels. In the present work, Ni-doped Ca2Fe2O5...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…An extensively investigated topics is methane to syngas/H 2 conversion. 95,[109][110][111][112][113][114][115][116][117]123,[125][126][127]130,136,185,[193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208] A few other studies explored a phase transition sorbent concept where a single mixed oxide particle combines the function of a redox oxide (for oxygen separation), a carbonate sorbent (for CO 2 separation), and a catalyst (to catalyze chemical reactions). 95,123,130,197,198,[209][210][211] For instance, a recent study adopted the chemical looping strategy to selectively oxidize ammonia with excellent NO selectivity for nitric acid production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensively investigated topics is methane to syngas/H 2 conversion. 95,[109][110][111][112][113][114][115][116][117]123,[125][126][127]130,136,185,[193][194][195][196][197][198][199][200][201][202][203][204][205][206][207][208] A few other studies explored a phase transition sorbent concept where a single mixed oxide particle combines the function of a redox oxide (for oxygen separation), a carbonate sorbent (for CO 2 separation), and a catalyst (to catalyze chemical reactions). 95,123,130,197,198,[209][210][211] For instance, a recent study adopted the chemical looping strategy to selectively oxidize ammonia with excellent NO selectivity for nitric acid production.…”
Section: Discussionmentioning
confidence: 99%
“…52–94 Furthermore, marrying the chemical looping strategy with oxidative catalysis offers a unique opportunity to intensify the production of a few important commodity chemicals with substantially decreased energy consumption and CO 2 emissions. 95–136 Given that separation processes consume ∼60% of the total energy usage in chemical and petroleum industries and heterogeneous catalysts are responsible for >80% of all chemical products worldwide, chemical looping catalysis (CLCa) in this article, has the potential to facilitate process intensification throughout the chemical manufacturing sector by combining catalytic reactions with separations. 120,137–142 The abovementioned chemical looping process types are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Although renewable energy sources are receiving widespread attention due to their carbon-free operation, fossil fuels remain the primary energy source in several countries . To ensure engineering makes net-positive contributions to environmentally friendly and economical process development, especially for fossil fuel utilization, innovative approaches are required to reduce the emission of pollutants while continuing the utilization of fossil fuels. Furthermore, due to rapid advancements in fracking technology, CH 4 production has steeply risen, and its utilization has recently gained widespread attention for producing energy or value-added products employing a carbon-neutral or carbon-negative process scheme. Though CH 4 is a cleaner fossil fuel than coal, its overproduction until now has led to colossal energy wastage due to flaring. Chemical looping (CL) is an advanced technology that has shown responsible utilization of CH 4 alongside CO 2 capture. The technology is based on splitting a reaction into subreactions to minimize exergy loss and maximize operational flexibility. These subreactions involve reaction intermediates termed as oxygen carriers (OCs) that react and are regenerated cyclically.…”
Section: Introductionmentioning
confidence: 99%
“…, Ni or Cu species) on perovskite ferrites enables accelerated reaction kinetics by promoting methane activation and surface oxygen exchange. 31–34 The above results showed that modulating the metal–oxygen interaction by nanotechnology is effective in enhancing selective anaerobic oxidation of methane; however, developing an effective method to restrain the sintering of these nanoparticles or active metals remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports demonstrate that decoration of reactive metals (e.g., Ni or Cu species) on perovskite ferrites enables accelerated reaction kinetics by promoting methane activation and surface oxygen exchange. [31][32][33][34] The above results showed that modulating the metal-oxygen interaction by nanotechnology is effective in enhancing selective anaerobic oxidation of methane; however, a CAS Key Laboratory of Science and Technology on Applied Catalysis, Dalian Institute of Chemical Physics, Chinese Academy of Sciences, Dalian 116023, China. E-mail: xdwang@dicp.ac.cn; huangchuande@dicp.ac.cn b College of Chemical Engineering, Northwest University, Xi'an 710069, China.…”
Section: Introductionmentioning
confidence: 99%